Product patents and access to innovative medicines in a post-trips-era - Jayashree Watal; Rong Dai (World Trade Organization (WTO), 2019)
This WTO working paper studies availability and affordability of new and innovative pharmaceuticals in a post-TRIPS era. The WTO's TRIPS Agreement (TRIPS) makes it obligatory for WTO members − except least-developed country members (LDCs) - to provide pharmaceutical product patents with a 20-year protection term. Developing country members, other than LDCs, were meant to be compliant with this provision of TRIPS by 2005. This study investigates two questions in this context: (1) How does the introduction of product patents in pharmaceuticals affect the likelihood of pharmaceutical firms to launch new and innovative medicines in those markets? (2) For launched new and innovative medicines, how much do patent owners or generic pharmaceutical firms adjust their prices to local income levels? Using launch data from 1980 to 2017 covering 70 markets, the study finds that introduction of product patent for pharmaceuticals in the patent law has a positive effect on launch likelihood, especially for innovative pharmaceuticals. However, this effect is quite limited in low-income markets. Also, innovative pharmaceuticals are launched sooner than non-innovative ones, irrespective of the patent regime in the local market. Using a panel data set of originator and generic prices from 2007 to 2017, the study finds evidence of differential pricing for both originator and generic products. Overall, originators differentiate by about 11% and generics by about 26%. Differential pricing is larger for pharmaceuticals to treat infectious diseases, particularly for HIV/AIDs medicines, than for non-communicable diseases. However, pharmaceutical prices are far from being fully adjusted to local income levels in either case. However, competition, especially that within a particular medicine market, can effectively drive down prices in both originator and generic markets.
Keywords: O34; I11; I19; F19; 330; intellectual property rights; patents; TRIPS; pharmaceuticals; pharmaceutical prices; differential pricing; developing countries